Prevalence of Depression and Anxiety Symptoms in A Sample of Christian Denominations: A Study From South Africa - Mokwena, Kebogile; Maaga, Khomotso; Ramatsui, Oria; Ngema, Vukile Msizi; Ravhengani, Machaka (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
The rising global prevalence of mental disorders, particularly depression and anxiety, underscores the urgent need to assess their burden within communities. Faith-based groups represent a unique population for such assessments as they include diverse segments of society while also functioning as significant social and spiritual support systems. This study aimed to determine the prevalence of depressive and anxiety symptoms among members of Christian denominations in South Africa. A quantitative cross-sectional survey was conducted across various provinces, and data were collected using the Patient Health Questionnaire (PHQ-9) and the Generalized Anxiety Disorder Scale (GAD-7). A total of 508 participants constituted the final sample. The findings revealed a prevalence of 40.94% for depression and 38.98% for anxiety symptoms. Inferential analysis indicated significant associations between gender, number of dependents, and frequency of church attendance with both depression and anxiety symptoms (p≤0.05). These results highlight the elevated burden of mental health symptoms within faith-based populations, exceeding previously reported rates in the general population. The findings emphasize the importance of integrating mental health awareness and support into church settings to reduce stigma, provide targeted interventions, and promote family and community well-being within South Africa.